2020
DOI: 10.1093/biolinnean/blaa035
|View full text |Cite
|
Sign up to set email alerts
|

Platysace (Apiaceae) of south-western Australia: silent story tellers of an ancient human landscape

Abstract: High gene flow and a population structure corresponding to human rather than geographical drivers are likely to be genetic patterns of human-dispersed plant taxa. We examined variation in geographical structure and gene flow estimates based on three non-coding regions of plastid DNA in three south-west Australian members of the Platysace genus to identify whether a human influence on dispersion of utilized taxa was detectable. Edible tubers of Platysace deflexa and Platysace trachymenioides have been harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…The LES population, which is the northmost population, displays mixed affinity, being similar to both southern (green) and northern (yellow and red) populations. This is consistent with the northern areas harbouring ancestral variation in other co‐occurring species (e.g., marri; Sampson et al, 2018 ), or could indicate possible historic human influence through Aboriginal movement of plants (Lullfitz et al, 2020 ; Lullfitz, Dabb, et al, 2020 ).…”
Section: Resultssupporting
confidence: 72%
“…The LES population, which is the northmost population, displays mixed affinity, being similar to both southern (green) and northern (yellow and red) populations. This is consistent with the northern areas harbouring ancestral variation in other co‐occurring species (e.g., marri; Sampson et al, 2018 ), or could indicate possible historic human influence through Aboriginal movement of plants (Lullfitz et al, 2020 ; Lullfitz, Dabb, et al, 2020 ).…”
Section: Resultssupporting
confidence: 72%
“…In an earlier study (Lullfitz et al 2021a), we found that harvest of Platysace deflexa tubers promoted population renewal, which aligns with LK's observation of its prominence in disturbed gravel pits. The many references to Noongar carrying of USOs when travelling also concurs with genetic homogeneity among P. deflexa and P. trachymenioides populations found by Lullfitz et al (2020), and suggests that Noongar use of some USO resources may have influenced current population distributions, and even expanded their range.…”
Section: Conservationsupporting
confidence: 62%
“…Indigenous Australians have occupied the Pilbara for at least 50 thousand years [ 113 ] and may have been important dispersers of some plant species [ 114 ]. Relatively little recognition has hitherto been given to the potential impacts of this means of dispersal on the present distributions of species and their genetic diversity, but it is likely that people have impacted the current biogeography of plant species, mobilising them for their use as food, medicine or for totemic purposes [ 114 , 115 , 116 , 117 ]. Combined with extreme meteorological events, these features provide a context for understanding the LDD observed in widespread Pilbara plant species and can form the basis of future hypotheses regarding genetic connectivity amongst the Pilbara flora.…”
Section: Discussionmentioning
confidence: 99%